Inside lining steel sheet subassembly and use coal bunker of this subassembly - TIAN GUIFENG (2018)
The utility model discloses an inside lining steel sheet subassembly and use coal bunker of this subassembly, including a many pitch cone shape steel sheet section of thick bamboo, the lower edge of the going up a lesson steel sheet section of thick bamboo inboard on the last edge of next knotted bar iron board section of thick bamboo of pegging graft, the opening is followed down in upward beinggreater than along the opening of every knotted bar iron board section of thick bamboo, the bottom inclination of a steel sheet section of thick bamboo is 75. The utility model discloses simple structure convenient to use is suitable for super dark coal bunker and uses, closes up in the bottom of avoiding the impact force to cross the whole coal bunker of havoc, can guarantee the working face andnormally mine, realizes not stopping work production simultaneously. 本实用新型公开了种内衬钢板组件及使用该组件的煤仓，包括多节锥形钢板筒，上节钢板筒的下沿插接到下节钢板筒的上沿的内侧，所述每节钢板筒的上沿开口大于下沿开口，所述钢板筒的底部倾斜角度为75°。本实用新型结构简单使用方便，适合于超深煤仓使用，避免冲击力过大破坏整个煤仓的底部收口，能够确保工作面正常采煤，同时实现不停工生